Digital Character Management: Building the Indonesian Language in the Era of Society 5.0 - Ali, Muttaqin Kholis; Ali, Fitri Furqoni (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This research aims to explore the role of the Indonesian language in shaping digital character in the Society 5.0 era. Through a qualitative approach, this study analyzes various approaches in scientific research related to digital character governance. The results show that character education in the digital era faces challenges and opportunities. Digital literacy, technology-based learning, and social media usage have significant impacts on shaping students' characters. The Indonesian language curriculum needs to be updated to include aspects of digital literacy and the ethics of technology usage. Strengthening collaboration between schools, families, and communities is also necessary to build positive digital characters. Recommendations for the development of digital character through the Indonesian language include enhancing the digital literacy of teachers and students, curriculum adjustments, promoting positive social media usage, and strengthening collaboration among stakeholders. Further research can explore innovative teaching methods in technology-based Indonesian language learning and the long-term impacts of digital literacy integration in Indonesian language education on student character development.Keywords: Digital Character, Governance, Indonesian Language, Society 5.0